Evaluasi Pengendalian Intern Persediaan Pipa Distribusi Dan Accessories Dalam Mengamankan Asset Perusahaan Pada PDAM Tirta Pakuan - Budianto, Enjang Tachyan; Setiawan, Hendra (STIE Kesatuan, 2009)
The purpose of this study was to evaluate whether the internal control system in securing supply company asset have been carried out properly and in accordance with the generally accepted in Indonesia and accordance with procedures issued by the companies concerned. Research conducted in the PDAM Tirta Pakuan Bogor. Water is a company engaged in the processing of drinking water and as the largest producer in Bogor. The result showed PDAM Tirta Pakuan Bogor has done internal control and securing supplies company with good assets. And the control is quite justifiable to serve as the basis in making decisions that are presented in the balance sheet value. Control is done because each part in stock supply have their respective functions and existing inventories are used to fulfill customer needs so that existing stocks can be sufficient and no excess over stock. The result of the evaluation in this study showed that supplies in warehouse in accordance with the needs and storage is done by separating the types, quality and size so that if at any time would be hospitalization stock will easily do that because the goods are properly stored, this existing can be maintained properly and protected from any loss.